1994
DOI: 10.5144/0256-4947.1994.134
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori: Prevalence in 352 Consecutive Patients with Dyspepsia

Abstract: At the Riyadh Armed Forces Hospital (RAFH), 352 patients had gastroscopy and from each, antral gastric biopsies were taken for identification of Helicobacter pylori, by urease test and histopathology. In 217 (61.64%) of these 352 patients, the histology specimens showed Helicobacter pylori in 73.68% of patients with duodenal ulcer, 70% of patients with gastric ulcers and gastric erosions, 61% of patients with duodenitis and 52% of patients with gastritis. Helicobacter pylori, previously known as Campylobacter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Mohamed AE et al (41) 1994 382 61.64% H. p antrum Giemsa stain Ibrahim BH et al (38) 1995 286 81.7% H. p antrum Hand E Abdul Jabbar B et al (26) 1997 81 75.3% H. p (antrum ) different stain Asa'ad SK et al (9) 2000 50 84%…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohamed AE et al (41) 1994 382 61.64% H. p antrum Giemsa stain Ibrahim BH et al (38) 1995 286 81.7% H. p antrum Hand E Abdul Jabbar B et al (26) 1997 81 75.3% H. p (antrum ) different stain Asa'ad SK et al (9) 2000 50 84%…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…19 Chronic infection with H. pylori may lead to glandular atrophy and IM. 16,18,24,25,[33][34][35][36][37][38][39][40][41] It had been shown that the frequency of H. Pylori infection increased with advanced age. 19,20 This in agreement with the result of this study, where the number of H. Pylori positive case increased with advanced age also.…”
mentioning
confidence: 99%
“…Two antral biopsy specimens from each patient were fixed in 10% buffered formalin. Paraffin wax sections were cut after routine processing [4,10,11].…”
Section: Histological Analysismentioning
confidence: 99%
“…The incidence rate of H. pylori infection in chronic gastritis from various regions of Saudi Arabia ranges from 50% to 96%. [3][4][5] Men and women are equally affected by the infection. Six commonly used tests to detect H. pylori are the histological examination, microbial culture, poly-merase chain reaction, rapid urease test, serology (ELISA) and 13C-urea breath test.…”
Section: Ar Khan An Age-and Gender-specific Analysis Of H Pylori Inmentioning
confidence: 99%